Plasenta Previa : Mekanisme dan Faktor Risiko - Brian Rocky Ramadhan (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Placenta previa is a disorder that occurs during pregnancy that is characterized by the presence of placental tissue near or covering the cervix. Aim: Examine risk factors and their mechanisms in the formation of placenta previa. Method: This study is a literature review study, that researchers are looking for. Scientific sources were obtained from Google Scholar and Pubmed in the form of textbooks and scientific journals totaling 27 pieces. Results: Placenta previa risk factors, and showed association with advanced maternal age, parity, maternal smoking, infertility treatment, previous cesarean delivery, previous placenta previa, and recurrent abortion. Among these risk factors, some have increased over the past decade including cesarean section rates, advanced maternal age, and the number of women undergoing infertility treatment. Placenta previa is one of the obstetric emergencies and is a contributor to maternal mortality. Conclusion: That multiparity, a history of previous cesarean sections, and inadequate antenatal care are major risk factors. These risk factors may be useful for screening at-risk mothers. Adverse maternal and perinatal outcomes associated with placenta previa can be reduced by detecting the condition in the antenatal period with ultrasound before it becomes symptomatic.